Clinical Diagnosis and Multimodal Management of Rectal Prolapse in Buf faloes: From Chemical to Advanced Surgical Techniques (Indian Journal of Animal Production and Management, 2026)
Background: A problem of rectal prolapse in buffaloes is a severe  gastrointestinal emergency, which can cause great economic losses, unless  it can be addressed in good time. The objective of the study was to compare  the clinical diagnosis and multimodal treatment of the rectal prolapse in  buffaloes undergoing sophisticated surgical resection. Materials and Methods: The sample number was 50 female buffaloes (5  months to 13 years old) that received rectal protrusion. Clinical classification  was made, on the basis of the cases; most of the cases were Grade IV  (complete prolapse with necrosis or laceration), and 16% (n=8) were  incomplete cases. Surgical resection of the necrotic tissue was undertaken  under caudal epidural anesthesia (2% Lidocaine HCl), and a purse-string  suture and rectopexy were done afterwards. Results: The surgery produced a 100 % success rate with all the animals  being fully recovered after a period of 8 days after surgery. It was found  that the main predisposing factors were clinical manifestations of chronic  diarrhea, dysuria, and straining by roughage feeding. In Grade IV cases,  surgery was mandatory as the edema and tissue damage were severe. The  follow-up period did not show any complications or recurrences. Conclusion: Multimodal therapy comprising a surgical resection and  rectopexy is a very effective form of treating advanced rectal prolapse  (Grade IV) both in the calves and adult buffaloes. The surgical intervention  and standardized postoperative treatment such as antibiotics and diet  modification can guarantee an excellent prognosis.
Keywords: Rectal prolapse, Surgical resection, Buffalo, Grade IV prolapse, Rectopexy.